SHOCK ABSORBER - YAMASHITA Mikio (2025)
This shock absorber comprises: a cylinder; a divided member; a shaft-like member; a first flow path through which flows a fluid that has flowed out from one chamber among a first chamber and a second chamber; a second flow path, at least part of which is provided parallel to the first flow path; a first valve member which is provided to the first flow path and via which fluid in said one chamber can flow into the other chamber; a partition wall member which has a wall part and a bottom part, through which the shaft-like member passes, which is connected to the second flow path, and which forms a backpressure chamber that generates a force in the valve closing direction in the first valve member; a volume variation member which is disposed opposite from the bottom part and which, when deformed by the pressure of the fluid, can change the volume of the backpressure chamber; a seal member which forms a seal between said other chamber and the wall part; and a support member which directly or indirectly applies a biasing force to the first valve member and the volume variation member in the direction of separation. L'invention concerne un amortisseur comprenant : un cylindre ; un élément divisé ; un élément de type arbre ; un premier trajet d'écoulement à travers lequel s'écoule un fluide qui s'est écoulé à partir d'une chambre parmi une première chambre et une seconde chambre ; un second trajet d'écoulement, dont au moins une partie est disposée parallèlement au premier trajet d'écoulement ; un premier élément soupape qui est disposé sur le premier trajet d'écoulement et par l'intermédiaire duquel un fluide dans ladite chambre peut s'écouler dans l'autre chambre ; un élément paroi de séparation qui a une partie paroi et une partie inférieure, à travers lequel passe l'élément de type arbre, qui est relié au second trajet d'écoulement, et qui forme une chambre de contre-pression qui génère une force dans la direction de fermeture de soupape dans le premier élément soupape ; un élément de variation de volume qui est disposé à l'opposé de la partie inférieure et qui, lorsqu'il est déformé par la pression du fluide, peut modifier le volume de la chambre de contre-pression ; un élément d'étanchéité qui forme un joint d'étanchéité entre ladite autre chambre et la partie paroi ; et un élément de support qui applique directement ou indirectement une force de sollicitation au premier élément soupape et à l'élément de variation de volume dans la direction de séparation. この緩衝器は、シリンダと；分割部材と；軸状部材と；第一室および第二室のうちの一方から流出した流体が流れる第一の流路と；前記第一の流路と少なくとも一部が並列に設けられる第二の流路と；前記第一の流路に設けられて前記一方の室内の前記流体を他方の室内に流通可能な第一のバルブ部材と；壁部および底部を有し、前記軸状部材に貫通され、前記第二の流路に接続されて前記第一のバルブ部材に閉弁方向の力を発生させる背圧室を形成する隔壁部材と；前記底部に対向して配置され、前記流体の圧力により変形して前記背圧室の体積を可変させる体積可変部材と；前記他方の室と前記壁部との間をシールするシール部材と；前記第一のバルブ部材と前記体積可変部材とに離間方向の付勢力を直接的または間接的に印加する支持部材と；を有する。